Vaccination against Covid-19 — an analysis of Portuguese official sources’ digital health communication - Magalhães, Olga Estrela (2022)
The covid-19 pandemic poses complex challenges to governments and health authorities all around the globe. Institutions have to cope simultaneously with the efforts to control the dissemination of the disease and the need to undertake articulated health communication procedures. This communication process is challenging to manage, due to the considerable uncertainty of the available information, the increase in misinformation stemming from a scattered (and often unmediated) mediascape, and some social groups’ resistance to adhere to the recommended preventive measures. Vaccination emerges as a topic that fuels extreme positions — on the one side, the eagerness for vaccine availability (which encourages illicit attempts to get it); on the other, the obstinate refusal of vaccination (based on theories with no medical-scientific grounds). In this context, we aim to assess how the leading Portuguese governmental and health institutions communicate with their audiences in the digital environment through their official websites and online social networks. In five websites and four online social networks used by the chosen sources, we have collected the content about vaccination published between the announcement of the authorisation of the first vaccine and the beginning of the administration of the second round to health professionals. Then we have applied content analysis methodology to the corpus of this case study. The results have shown that the primary Portuguese official sources give themselves the floor regarding the covid-19 vaccination process, addressing three main themes using an eminently informative frame: vaccine administration, priority groups definition and a general approach to the vaccine. Bearing in mind health communication’s primary goals — engage, empower and influence citizens — we conclude that Portuguese official sources have promoted conservative forms of communication, potentially missing the opportunity to foster a more pedagogical and customised digital communication.